The Use of Visualization Strategy on Students’ Reading Comprehension: Is it Effective? - Sukmawati, Annisa; Baihaqi, Akhmad; Suharsih, Siti (Journal of Linguistics, Literacy, and Pedagogy, 2025)
The objective of this research is to find out the effect of using the visualization strategy on students’ reading comprehension in tenth grade at one senior high school in Serang City, Banten Province. This research used quasi-experimental design. The population in this research was all tenth grades students while the samples were from class X MIPA 4 as the experimental class and X MIPA 5 as the control class. The two classes were selected using purposive sampling. To obtain data, the researcher used pre-test and post-test as instruments consisting of 40 multiple choice items. The data obtained from both tests were analyzed using the T-test. The results of the post-test average scores show a significant increase between the pre-test and post-test. The average score in the pre-test of the experimental class is 60.5 while the control class got 59.5. In addition, the average score in the post-test experimental class is 80.33 while the control class is 72.00. The hypothesis tests reveal that sig. 2 tailed is 0.001 while the determined alpha (α) is 0.05 (5%). It means that sig. ≤ α or 0.001 ≤ 0.05. Therefore, it can be said that Ho is rejected and Ha is accepted. Thus, the visualization strategy is effective on students' reading comprehension.